2011
DOI: 10.1530/joe-11-0123
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotency-associated stem cell marker expression in proliferative cell cultures derived from adult human pancreas

Abstract: The source of new b-cells in adult human pancreas remains incompletely elucidated with recent studies on rodents providing evidence for neogenesis from progenitor cells in addition to self-replication. The aim of this study was to investigate the expression of pluripotency-associated stem cell markers in proliferative cultures derived from adult human pancreas. Human pancreatic tissue was obtained from deceased donors following ethical approval and relative consent. Isletenriched fraction was separated from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…Moreover, most evidence for the presence of stem/progenitor cell-like populations in nondissociated adult human pancreatic tissue has been limited to detecting equivocal stem cell marker expression in various pancreatic cell types (53,(55)(56)(57). Here for the first time, we report that b-cell stress/hyperglycemia stimulates an adult tissue progenitor cell population within human islets to proliferate and produce more insulin + progeny.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, most evidence for the presence of stem/progenitor cell-like populations in nondissociated adult human pancreatic tissue has been limited to detecting equivocal stem cell marker expression in various pancreatic cell types (53,(55)(56)(57). Here for the first time, we report that b-cell stress/hyperglycemia stimulates an adult tissue progenitor cell population within human islets to proliferate and produce more insulin + progeny.…”
Section: Discussionmentioning
confidence: 80%
“…Current regenerative approaches for treating human diabetes has concentrated almost entirely on the production of new b-cells from human pluripotent stem cell systems (52)(53)(54)(55). Moreover, most evidence for the presence of stem/progenitor cell-like populations in nondissociated adult human pancreatic tissue has been limited to detecting equivocal stem cell marker expression in various pancreatic cell types (53,(55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Oct-4 was found by another group in a low number of cells throughout the adult human pancreas [57]. The cells were very small (1.5–3 µm) and could be described as VSELs, but Oct-4 staining was visible only in cytoplasm [57]. Finally, analysis of methylation of Oct-4 promoter may indicate an active transcription of the gene but is not clear whether it can reveal the specific expression of Oct-4A.…”
Section: Discussionmentioning
confidence: 99%
“…Although Oct-4A is present mostly in nucleus and Oct-4B preferentially localizes to cytoplasm, the localization itself cannot be treated as isoform marker, because Oct-4B can also display nuclear translocation [53], [55]. Interestingly, Oct-4 was found by another group in a low number of cells throughout the adult human pancreas [57]. The cells were very small (1.5–3 µm) and could be described as VSELs, but Oct-4 staining was visible only in cytoplasm [57].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies have shown SOX2 deregulation in different human cancer types. 18, 19, 20, 21, 22, 23, 24 Several studies present evidence for the presence of SOX2 in stem cell-like progenitor cells in the adult human pancreas , 25, 26 but the function of SOX2 in pancreatic cancer remains unknown.…”
Section: Introductionmentioning
confidence: 99%